PENGARUH DEWAN KOMISARIS DAN KOMITE AUDIT TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (STUDI EMPIRIS PERUSAHAAN HIGH PROFILE DI BURSA EFEK INDONESIA) - Rivandi, Muhammad; Putra, Andi Harita (LPPM Press STIE Indragiri Rengat, 2019)
ABSTRACT   This study aims to examine the effect of the Board of Commissioners and the Audit Committee on the Disclosure of Corporate Social Responsibility (Empirical Study on High Profile Companies on the Indonesia Stock Exchange 2013-2017). The method of data collection is done by documentation of data sourced from annual reports published through the Indonesia Stock Exchange. The sample in this study were 42 companies listed on the Indonesia Stock Exchange which were selected using purposive sampling. The analytical method used was a panel regression model. Data is tested using Eviews software version 8.0. Based on the hypothesis the test results show that the board of commissioners has no effect on disclosure of corporate social responsibility while the audit committee has a positive and significant effect on corporate social responsibility.   Keywords: Board of Commissioners, Audit Committee, Corporate Social Responsibility of dicclosure